2018
DOI: 10.21873/invivo.11132
|View full text |Cite
|
Sign up to set email alerts
|

Netrin-4 Promotes Differentiation and Migration of Osteoblasts

Abstract: Background/Aim: While netrin-4 plays a vital role in the vascular system, the role of netrin-1 in osteoblast differentiation is not well understood. In this study we explored whether netrin-4 has functional roles in osteoblasts. Materials and Methods: Quantitative reverse-transcriptase polymerase chain reaction (PCR), RNA interference, the generation of plasmids, transfections, measurement of alkaline phosphatase activity, a mineralization assay, a migration assay and a cell proliferation assay were performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Bone formation, remodeling, and maintenance are a physiologically complex process, and a series of events occur including cell migration of osteoblast lineage cells [37,38]. It is well known that the Wnt/β-catenin signaling pathway participates in the regulation of cell migration and differentiation [28,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Bone formation, remodeling, and maintenance are a physiologically complex process, and a series of events occur including cell migration of osteoblast lineage cells [37,38]. It is well known that the Wnt/β-catenin signaling pathway participates in the regulation of cell migration and differentiation [28,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…The recently identified DJ‐1 protein is a novel osteogenic factor that promotes the osteogenesis of MSCs through the activation of FGF signalling. 21 Additionally, recent studies showed that Thy‐1, 22 , 23 netrin 4 24 and retinol‐binding protein 1 25 are positive regulators of osteoblast differentiation. These results indicate that CME contains numerous known osteogenic stimulators or osteogenic regulatory proteins, which might be why CME has osteogenic properties in hMSCs.…”
Section: Resultsmentioning
confidence: 99%
“…More recent data show that, also, Netrin-4 may link angiogenesis and bone remodeling. Endothelial Netrin 4 inhibits osteoclast differentiation in vitro and showed osteoprotective effects in an osteoporotic mouse model [ 36 ], but the effect of Netrin-4 does not seem to be limited to osteoclasts, as Netrin-4-dependent differentiation and migration of osteoblasts were also shown [ 37 ].…”
Section: Bone Remodelingmentioning
confidence: 99%